Work Practices of Older Population Groups: Reasons for Choice - Kartuzova, Maria (Journal of Economic Sociology, 2020)
The most important challenge for developed and developing countries of the 21st century, in the opinion of the United Nations, is increasing lifespans alongside fertility reduction. This is shown to result in the maintenance of older people’s health and labor activity at an average level. At the same time high developed IT leads to a growing sharing economy. This results in labor market changes and global digitalization of the economy compounds this. At the same time the economic crises lead to reducing household incomes. There are a lot of older population groups in the labor market at an age when their parents had already retired, so youth unemployment stems from older people competing with younger for jobs. Aggressive ageism is one of the characteristics of such a situation. Governments are paying people to retire later. As a result, the labor market consists of senior employees who are trying to give their family an acceptable standard of living even if they are old enough to retire, and young and middle-aged employees. These groups compete with each other, and the more heterogeneous the labor force, the more intense the competition becomes. As a result, countries propose political programs to reduce the negative impact of the demographic crisis. For Russia this problem is also a current problem. But Russia is beginning its path. It needs to interpret the experiences of Western countries and choose its own way. This article offers a detailed examination of the labor practices of older population groups. The first labor practice investigated is leaving the labor market, the second is employment and the third is self-employment, including entrepreneurship. The author shows how the classification of causes leads to the choice of a specific strategy at labor market. She theorizes that neoliberalism gives older people a new ability to help country economy, rather than being disability recipients. As a result, the author concludes that although the problem of the aging population in Russia and in developed countries is the same, but a common practice is not suitable. And the new Russian pension reform that increases the retirement age may lead to a national catastrophe as older people have difficulties to find work and have no cash savings.